Simple coppice management options for the sal (Shorea robusta Gaertn. f.) forests in the Terai of Nepal - Ojha, SK; Acharya, KP; Acharya, B; Regmi, R (Banko Janakari, 2009)
<!--[if gte mso 9]> Normal 0 false false false MicrosoftInternetExplorer4 <![endif]--><!--[if gte mso 9]> <![endif]--><!--[if !mso]> <![endif]--> <!--[if gte mso 10]> <![endif]--> The paper examines simple coppice management options for sal (Shorea robusta Gaertn. f.) forest that maximizes total biomass production. The study is based on the data obtained from two non-replicated research blocks located at Butwal and Dharan, which were established in 1988 and 1989 respectively by the Department of Forest Research and Survey. Out of four blocks in each site, one block was of simple coppice management option. Simple coppice management option had four treatments, i.e. 1) 3 s/s, 2) 1 s/s, 3) 3-2-1 s/s, and 4) Control, which were designed for fodder and fuelwood production in a short rotation of four years. The analysis was done to estimate the productivity of the treatments for the four successive rotations. In on average, it was found that treatment 3- 2-1 s/s was the best to produce maximum biomass in short rotations. Both treatments 1 s/s and 3-2-1 s/s were found best for foliage production. Local community user groups benefit from the result to choose appropriate simple coppice management option in their sal forests, if fodder and fuelwood production in short rotations is the main objectives of the forest management. Key words: biomass, coppice, Nepal, regeneration, Sal forests. doi: 10.3126/banko.v18i1.2164 Banko Janakari, Vol. 18, No. 1, 32-41